2006
DOI: 10.1093/ndt/gfl538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statin treatment on renal function and serum uric acid levels and their relation to vascular events in patients with coronary heart disease and metabolic syndrome: A subgroup analysis of the GREek Atorvastatin and Coronary heart disease Evaluation (GREACE) Study

Abstract: Among CHD patients, those with MetS benefited more from statin treatment than those without MetS. This benefit could be partially attributed to favourable changes in e-GFR and SUA levels probably induced by statin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
111
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(120 citation statements)
references
References 37 publications
7
111
0
2
Order By: Relevance
“…These results come in agreement with other studies demonstrating that multifactorial treatment, including statin therapy, may have a favourable impact on liver and kidney function. [28,29] Nevertheless, the most potent therapies were not preferred in our study. High-dose statin treatment was not used, while only 20% of the subjects were receiving combination treatment of statin + ezetimibe.…”
Section: Strategies Confronting Poor Multi-factorial Target Attainmentmentioning
confidence: 82%
“…These results come in agreement with other studies demonstrating that multifactorial treatment, including statin therapy, may have a favourable impact on liver and kidney function. [28,29] Nevertheless, the most potent therapies were not preferred in our study. High-dose statin treatment was not used, while only 20% of the subjects were receiving combination treatment of statin + ezetimibe.…”
Section: Strategies Confronting Poor Multi-factorial Target Attainmentmentioning
confidence: 82%
“…In support of a beneficial role for statins in ameliorating the progression of diabetic nephropathy, several clinical studies have reported findings of a preserved glomerular filtration rate and diminished urine albumin excretion in diabetic patients with proteinuria treated with statins (18,20,24,45,46). However, the molecular mechanism(s) responsible for the renoprotective effects of statins has been the subject of much debate.…”
Section: Discussionmentioning
confidence: 99%
“…Multifactorial treatment has several beneficial effects on both CVD and renal function, especially in high-risk patients such as those with MetS 36 and CKD 4,5 . Of note, statins were also shown to reduce SUA levels 37,38 . Antihypertensive treatment and especially drugs that block RAAS (i.e., converting enzyme inhibitors, angiotensin and aldosterone receptor antagonists) exert beneficial cardiovascular and renal effects 39 ; improvements in proteinuria as well as prevention of CKD progression, CVD morbidity and mortality have been reported in relation to such antihypertensive therapy [40][41][42] .…”
Section: I a L D I S T R I B U T I O N U N A U T H O R I Z E D U S mentioning
confidence: 99%